2014
DOI: 10.1038/bmt.2014.235
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing drug therapy in pediatric SCT: Focus on pharmacokinetics

Abstract: Given age-related differences in drug metabolism and indications for hematopoietic stem cell transplantation (HSCT), personalized drug dosing of the conditioning regimen and post-transplant immunosuppression may reduce graft rejection, relapse rates, and toxicity in pediatric HSCT recipients. This manuscript summarizes the pharmacokinetic/dynamic data of HSCT conditioning and postgrafting immunosuppression, presented at the First Annual Pediatric Bone Marrow Transplant Consortium meeting in April 2013. Persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 87 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…The findings of our study might thus be explained by the reduced efficacy of PTCY in clearing alloreactive T cells in younger children coupled with variable MMF metabolism, which are probably attributable to the differing metabolisms of these drugs in younger children as exemplified in the PK studies . Unfortunately, PK data are not available in this cohort of patients as they were not a part of the original study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The findings of our study might thus be explained by the reduced efficacy of PTCY in clearing alloreactive T cells in younger children coupled with variable MMF metabolism, which are probably attributable to the differing metabolisms of these drugs in younger children as exemplified in the PK studies . Unfortunately, PK data are not available in this cohort of patients as they were not a part of the original study.…”
Section: Discussionmentioning
confidence: 90%
“…The age of the children in this cohort varied between two and 15 yr. On the other hand, another PK study of high-dose CY in children above the age of 10 yr undergoing myeloablative conditioning for solid tumors did not reveal any impact of age on clearance or the volume of distribution of CY (21). It is possible that a dosing based on body weight might not be optimum in younger children (22). The other contributing factor could have been related to the PK s of MMF in younger children (23).…”
Section: Discussionmentioning
confidence: 98%
“…MPA pharmacokinetics has been extensively studied in adult reduced-intensity transplants; however, the data in myeloablative transplants, especially in the pediatric age group, is very limited (reviewed in McCune et al [20]). Although retrospective studies have shown correlation between MPA levels and risk of aGVHD and there is a large inter-and intrapatient pharmacokinetic variability, MMF continues to be used on a fixed-dose schedule [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Proper characterization of age-dependent pharmacokinetics is particularly important to alloHCT as newborn screening techniques are leading to earlier diagnosis of immunodeficienicies and, in turn, younger alloHCT recipients. 171 The expression of drug clearance relative to BSA appears to be the most appropriate method for comparing clearance in children of varying ages. 172 The current practice of linearly dividing dose by body weight does not reflect the true nature of the relationship between clearance and dosing weight.…”
Section: Discussionmentioning
confidence: 99%